2017
DOI: 10.1177/1474515117708888
|View full text |Cite
|
Sign up to set email alerts
|

Frailty assessment instruments in heart failure: A systematic review

Abstract: Background: Frailty is an independent predictor of mortality across many conditions. Reported rates of frailty in heart failure range from 15% to 74%. There are several instruments available to assess frailty; however, to date there has been no consensus on the most appropriate instrument for use in individuals with heart failure. Aims: To identify how frailty is assessed in individuals with heart failure and to elucidate which domains of frailty are most frequently assessed. Methods: Key electronic databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 65 publications
(107 reference statements)
0
59
0
1
Order By: Relevance
“…The term fragility may be used to describe slightly different settings; yet from a strict geriatric perspective, it means an increased risk of disability. Indeed, our approach has been included as the Comprehensive Geriatric Assessment instrument in a recent comprehensive review by McDonagh et al 6 . Most patients were referred from the cardiology department and had ischemic heart disease as the cause of HF, and the study population was relatively young, with a small percentage of women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term fragility may be used to describe slightly different settings; yet from a strict geriatric perspective, it means an increased risk of disability. Indeed, our approach has been included as the Comprehensive Geriatric Assessment instrument in a recent comprehensive review by McDonagh et al 6 . Most patients were referred from the cardiology department and had ischemic heart disease as the cause of HF, and the study population was relatively young, with a small percentage of women.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, QOL is related to fragility in the full age spectrum of patients with HF 5 . Notably, there is still no universal definition of fragility; thus, there are no fully standardized methods for measuring it, although several tools are increasingly used in recent times 6 . We started to assess fragility almost 2 decades ago in ambulatory patients with HF using a set of validated geriatric scales as surrogates of fragility,3, 5 and with these scales we have shown that fragility is a key determinant for the prognosis of patients with HF of all ages 7 …”
mentioning
confidence: 99%
“…In an attempt to overcome these weaknesses, several other instruments have been developed over time, through changing, omitting or adding criteria to one or the other of these two conceptual definitions or using single components of the physical frailty phenotype. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The main characteristics and limitations of the main frailty assessment instruments used in HF patients are shown in Table 1.…”
Section: Overview Of Frailty Definition and Assessment Toolsmentioning
confidence: 99%
“…Although the concept of frailty is extensively used, in clinical and research settings, an internationally accepted definition is still lacking and there is no agreement on which is the best method or instrument to assess frailty. Several definitions of frailty and a plethora of different instruments have been used for the identification of frailty within a variety of disease states and settings . This has limited the possibility not only to ‘speak a common language’ and to compare the results from different studies, but has challenged the possibility for correct diagnosis and interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation